Focal Epilepsy and the Clock Gene - Roberto Refinetti (Pediatric Neurology Briefs Publishers, 2018)
Investigators from Children's National Medical Center, Wenzhou Medical University, Virginia Tech, University of Colorado, University of Virginia, Georgetown University, University of Maryland, and Brown University performed transcriptome analysis on human epileptogenic tissue and extended the investigation by creating and testing mouse lines with targeted genetic deletions of the Clock gene.